DETEKSI DAN EDUKASI KESEHATAN MENTAL DI MASA PANDEMI COVID-19 PADA REMAJA KOTA PALANGKA RAYA - Wahyuni, Seri; Sukriani, Wahidah (LPPM Institut Pendidikan Nusantara Global, 2024)
Teenagers are the most vulnerable age group to experience stress and anxiety when faced with a new problem due to the COVID-19 outbreak. The purpose of this activity is to conduct early detection and mental health education during the Covid-19 pandemic for adolescents in Palangka Raya City. The method used in this activity is early detection of mental health with the Patient Health Questionnaire-9 (PHQ-9) followed by mental health education for adolescents. The results of this activity are 23.33% of adolescents who do not experience depression, 53.34% of mild depressive symptoms, and 23.33% of mild symptoms. encourage adolescents to share their feelings, take the time to provide support to adolescents, work together to resolve conflicts , educating youth to love themselves, reducing negative news viewing, sports/physical activities together, using social media wisely.